A comprehensive study on CFRP rapid portable bridge: Design, experimental investigation and finite element analysis. (1st June 2022) - Xiong, Jianwu; Ai, Pengcheng; Xu, Jin; Yang, Jia-Qi; Feng, Peng
Abstract: For military and emergency applications, there is the high demand for bridges that are light-weight, high-strength, and easy to transport and install. Carbon fiber-reinforced polymer (CFRP) composites are promising for rapid portable bridges due to their excellent performance. A CFRP rapid portable bridge (CRPB) with a box beam profile was designed in this study, and a 1:2.5 scaled model of the CRPB was manufactured and tested under track loads to evaluate its structural performance. The failure mode of the CRPB was crushing of the bridge upper deck, and the ultimate load was 6.5 times the design strength. Tensile joints performed well in the test without obvious damage and were an effective connection strategy. The mechanical behavior of the shear keys and tensile joints were studied by finite element methods. The numerical results from the finite element analysis of CRPBs show good agreement with the experimental results.